Lexical Syntax for Arabic SMT - Hassan Awadalla, Hany (Challenges for Arabic Machine Translation, 2012)
The current approaches of Phrase-based Statistical Machine Translation lacks the capabilities of producing grammatical translations and handling long-range reordering.